2021
DOI: 10.1002/bies.202100207
|View full text |Cite
|
Sign up to set email alerts
|

Skin aging: Dermal adipocytes metabolically reprogram dermal fibroblasts

Abstract: Emerging data connects the aging process in dermal fibroblasts with metabolic reprogramming, provided by enhanced fatty acid oxidation and reduced glycolysis. This switch may be caused by a significant expansion of the dermal white adipose tissue (dWAT) layer in aged, hair-covered skin. Dermal adipocytes cycle through dedifferentiation and re-differentiation. As a result, there is a strongly enhanced release of free fatty acids into the extracellular space during the de-differentiation of dermal adipocytes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…(66, 74) A critical step in AMT is the release of free fatty acids into the local tissue environment, a process which permits the transition of a lipid droplet-containing adipocytes into a precursor cell. (20) Lipolysis is thought to be the primary mechanism by which free fatty acids are released by the DWAT. (21,75) To our knowledge, nothing is known about whether SIX1 also promotes fatty acid turnover in vivo; however, studies have shown that SIX1 promotes metabolic shifts in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(66, 74) A critical step in AMT is the release of free fatty acids into the local tissue environment, a process which permits the transition of a lipid droplet-containing adipocytes into a precursor cell. (20) Lipolysis is thought to be the primary mechanism by which free fatty acids are released by the DWAT. (21,75) To our knowledge, nothing is known about whether SIX1 also promotes fatty acid turnover in vivo; however, studies have shown that SIX1 promotes metabolic shifts in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…(17)(18)(19) They can cycle through de-differentiation and redifferentiation as part of a physiologic response to hair cycling, aging, and energy demands. (17,18,20) Under certain conditions, de-differentiated pre-adipocytes escape the normal cycle of redifferentiation, and trans-differentiate into ECM-producing myofibroblasts. This process is referred to as the adipocyte-to-myofibroblast transition (AMT).…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that SCA ® treatment increases procollagen-1 secretion in senescent cells, reducing the aged phenotype provoked by H 2 O 2 . Importantly, the deposition and maintenance of ECM, serviced by competent cells, is an input as essential as circulating growth factors to ensure tissue repair and health [ 55 , 56 , 57 , 58 , 59 ], and likely contributes to the curbing of tissue aging.…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal cells significantly elevate their mitochondrial uptake of fatty acids and enhance β-oxidation in an infection-induced model of cutaneous inflammation, contributing to the recruitment of leucocytes [ 76 ]. Release of fatty acids by de-differentiating adipocytes significantly modifies the metabolic substrates processed by keratinocytes and fibroblasts, thus providing a strong impetus for their metabolic reprogramming [ 5 , 6 ]. Such reprogramming significantly influences the synthetic and proliferative capacities of these cells.…”
Section: How Are Cellular Dedifferentiation Events In Dwat Involved I...mentioning
confidence: 99%
“…De-differentiation of dermal adipocytes into ADPs in the catagen is accompanied by a significant reduction of their volumes and leads to loading of the dWAT and reticular dermis with fatty acids [ 5 , 6 ]. Re-differentiation of preadipocytes in anagen leads to a regain of the cell volumes and causes intensive expression of the anti-microbial peptide cathelicidin.…”
Section: Introductionmentioning
confidence: 99%